Ultrasensitive determination of sulfathiazole using a molecularly imprinted electrochemical sensor with CuS microflowers as an electron transfer probe and Au@COF for signal amplification. (1st December 2020) - Sun, Yufeng; Gao, Huiju; Xu, Longhua; Waterhouse, Geoffrey I.N.; Zhang, Hongyan; Qiao, Xuguang; Xu, Zhixiang
Highlights: Copper sulfide as a novel active probe was used for ultrasensitive determination of sulfathiazole. Highly conductive gold nanoparticle@covalent organic framework was employed to enhance the Cu 2+ signal. A polypyrrole imprinted polymer for sulfathiazole recognition was prepared. This paper offers a promising analytical tool for ultrasensitive determination other analytes. Abstract: In this work, a molecularly imprinted sensor employing copper sulfide (CuS) as a novel signal probe was successfully developed for ultrasensitive and selective determination of sulfathiazole (STZ). The reduction signals of Cu 2+ produced in the process of electron transfer of CuS containing large amounts of Cu 2+ are easy to be captured, which provide high electrochemical signals. Moreover, gold nanoparticles@covalent organic framework with excellent conductivity was introduced on the electrode surface for signal amplification and facilitating electron transfer processes of CuS. Under optimized testing conditions, the proposed sensor offered a linear DPV response to STZ over a very wide concentration range (1.0 × 10 -4 to 1.0 × 10 -11 mol L -1 ), with a limit of detection of 4.3 × 10 -12 mol L -1 . Fodder and mutton samples spiked with STZ were analyzed using this sensor, and the satisfactory recoveries ranging from 83.0% to 107.2% were obtained. In addition, the proposed sensor was used to determine the concentration of STZ in chicken liver and pork liver, with quantification results being near identical to those determined by high-performance liquid chromatography.